ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Sudrajat, Widya Ariska; Yuniawan, Ahyar (Diponegoro Journal of Management, 2016)
An organization expects employees maximum performance results for the achievement of these goals. In achieving its performance is certainly needed positive work attitude of employees. so organizations should consider factors - factors that influence employee attitudes in order to achieve the desired goals of the organization. This research aims to; a) analyze the effect of incentives on employee job satisfaction; b) analyze the effect of incentives on employee performance; and c) to analyze the effect of job satisfaction on employee performance. The unit of analysis of this research is the employee who is in the production of PT. Kalinga Jati Jepara with an age range between 20 s / d 50 years and the minimum term of 1 year. Of the provisions of the analysis unit then found a population of some 70 employees, so that all of them were taken as samples through techniques census. From the results of hypothesis testing with SPSS shows that job satisfaction variable significant positive effect on employee performance. in addition, this study also uses data analysis method path analysis to examine the effect of mediation used Sobel Test. Sobel of the test carried out showed that the intrinsic motivation to work can not be an intervening variable between job satisfaction on performance variables. However, variable extrinsic motivation to work can serve as an intervening variable in order to influence job satisfaction on employee performance.